2021
DOI: 10.3389/fmars.2021.656282
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Fluctuation Attenuates the Effects of Warming in Estuarine Microbial Plankton Communities

Abstract: Sea surface warming has the potential to alter the diversity, trophic organization and productivity of marine communities. However, it is unknown if temperature fluctuations that ecosystems naturally experience can alter the predicted impacts of warming. We address this uncertainty by exposing a natural marine plankton community to warming conditions (+3°C) under a constant vs. fluctuating (±3°C) temperature regime using an experimental mesocosm approach. We evaluated changes in stoichiometry, biomass, nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…For instance, we found a positive antagonistic effect of warming under thermally varying conditions on Chromista morphology and physiology. Recent results have shown that thermal fluctuations promote transient “benign” conditions for organisms during cooling periods ( 40 ) and allow rapid phenotypic changes in metabolic traits and elemental composition ( 20 ) that accelerate the adaptation to warming stress. In addition, it is likely that studies testing the effect of global-change drivers under a constant regime tend to consider shorter experimental periods than those in which environmental fluctuations are also evaluated, thus overestimating the frequency of the interactive responses detected.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we found a positive antagonistic effect of warming under thermally varying conditions on Chromista morphology and physiology. Recent results have shown that thermal fluctuations promote transient “benign” conditions for organisms during cooling periods ( 40 ) and allow rapid phenotypic changes in metabolic traits and elemental composition ( 20 ) that accelerate the adaptation to warming stress. In addition, it is likely that studies testing the effect of global-change drivers under a constant regime tend to consider shorter experimental periods than those in which environmental fluctuations are also evaluated, thus overestimating the frequency of the interactive responses detected.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we did not consider warming‐induced changes in plankton size spectra, taxonomic composition and spatial distribution in this study. Although empirical data are relatively scarce outside of laboratory mesocosms and local studies (Benedetti et al, 2019; Cabrerizo et al, 2021; He et al, 2020; Murphy et al, 2020; Pulina et al, 2020), incorporating these information would yield more accurate model predictions whenever they are available. There are two specific directions for further implementations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, global changes caused by anthropogenic activities such as continuous press disturbances may impact differently on organisms that experience naturally variable or more constant environments. It has been proposed that warming effects on organisms' performance can be exacerbated by thermal fluctuations in comparison to warming effects under constant conditions (Wang et al 2019;Cabrerizo et al 2021;Gonz alez-Olalla et al 2022). However, water pH fluctuations under ocean acidification scenarios show less conclusive results, where negative, neutral, or positive effects on performance have been detected for corals and coralline algae when exposed to fluctuations under low pH (Cornwall et al 2013(Cornwall et al , 2018Rivest et al 2017).…”
Section: Terms and Definitionsmentioning
confidence: 99%